Crystalline silica particles exposure modulated miRNA expression profiles in human macrophage-like THP-1 cells - Evangel Kummari; Birgitte Lindeman; Unni C. Nygaard; Tellef Helle-Valle; Manosij Ghosh; Peter H.M. Hoet; Hubert Dirven; Nur Duale (Toxicology, 2026)

Natural deep eutectic solvents (NADES): dual functionality in the extraction and stabilization of polyphenols, terpenoids and nitrogen compounds - Gerardo Valles-Salas; Juliana Morales-Castro; Claudia I. Gamboa-Gómez; Blanca E. Morales-Contreras; Walfred Rosas-Flores; L. Araceli Ochoa-Martínez; Juan C. Contreras-Esquivel; Ana M. Ávila-Galván; Orlando A. Manzanares-Meza (Food Chemistry, 2026)

Ecological and genetic determinants of essential oil diversity in Mediterranean Thymus - José C. del Valle; Esther María Martín-Carretié; Francisco José García-Cárdenas; David Doblas; María Ángeles Ortiz; John Thompson; Perrine Gauthier; Bodil K. Ehlers; Diego Nieto-Lugilde; Regina Berjano (Biochemical Systematics and Ecology, 2026)

Bioacoustic Baselines for Intact Forests - Z. Buřivalová; S. Perea; L. M. Berman; H. S. S. C. Sagar; T. M. Maeda; N. Yoh; G. Ingram; M. Persche; C. Mere‐Roncal; A. Lopera‐Toro; E. Chaboteaux; R. Rumelt; et al. (Global Change Biology, 2026)
Forests are at the frontline of both climate and biodiversity crises: forests are fundamental to the regulation of Earth's atmospheric carbon dioxide levels, and tropical forests alone harbour over half of all terrestrial species. Consequently, forests are at the centre of global efforts to both prevent extinctions of species and sequester carbon to mitigate climate change. Most carbon sequestration initiatives do not measure how effective they are in terms of biodiversity protection, largely because it is expensive, complex and often not required. Compounding this problem is the lack of reliable biodiversity baselines, against which positive changes due to conservation and negative changes due to human pressure could be measured. The Soundscape Baselines Project is a global initiative to collect and analyse bioacoustic baselines in some of the world's remaining intact forests. The baseline data are collected using a modular system of passive acoustic monitoring and ancillary data that can be expanded and integrated with other technologies. It is managed by local teams of scientists, conservation practitioners and community members. Emphasis is on the usability of data and equipment beyond the project, community engagement and building an interconnected network of scientists across forested countries, particularly historically underexplored partnerships between tropical forest countries. In this paper, we describe the initiative and share initial results to demonstrate how the project could be used for biodiversity conservation purposes in the future and outline steps towards operationalization. We also draw a list of priority areas for additional baseline locations across remaining intact forests. We discuss how bioacoustic baselines established now and in the future will become invaluable in a rapidly changing climate and the resulting unprecedented change in Earth's forests. Establishing rigorous biodiversity baselines using bioacoustics and other technologies and approaches through collaborative science is fundamental to ground biodiversity conservation in evidence, equity and transparency.

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Wind-driven exchange flow and inter-basin connectivity in a multi-inlet bay during hurricane and non-hurricane periods - Wei Huang; Chunyan Li; Arnoldo Valle-Levinson; Daniel Gann; Michael C. Sukop; Jayantha T. Obeysekera; Tiffany Troxler (Ocean Modelling, 2026)

Adsorption-based direct air capture using hierarchical porous composites prepared via confined-space crystallization - Gabriela C. del Valle-Pérez; Juan Carlos Muñoz-Senmache; Sebastián Espiña-Santiago; Erick M. Mendez-Rios; Kim Kisslinger; Arturo J. Hernández-Maldonado (Chemical Engineering Journal, 2026)

Isolation of Leptolegnia chapmanii, an entomopathogenic oomycete, from Misiones, Argentina: a promising tool for vector mosquito control - Manuel E. Rueda-Páramo; Christina Schuster; Dario Balcazar; Flavia V. Diez del Valle; Alejandra C. Gutierrez; Anna Heitmann; Oscar D. Salomon; Andreas Leclerque (BioControl, 2026)

Sex Drives Intraspecific Scaling of Home Range Size in Mammals - Aline Giroux; Denis Valle; Eliezer Gurarie; Marcus Vinicius Vieira; James D. Forester; Luca Börger; Raissa Sepulvida; Nicole Barbour; Erika G. da Rocha; Julia Oshima; Fernanda C. de Azevedo; Frederico G. Lemos; et al. (Ecology Letters, 2025)
Understanding variation in home range size (HR) provides important insights into the underlying ecological processes driving space use. However, it remains unclear whether the interspecific allometric scaling of mammals' HR can also be consistently observed within species and for both sexes. To address this knowledge gap, we GPS‐tracked 349 resident individuals across Brazil, encompassing 18 mammal species. We estimated individuals' HR and modelled intraspecific variation in HR against body mass (BM) and sex. While males showed a positive allometric scaling similar to interspecific findings reported in the literature (exponent = 1.23), females' BM had no statistically discernible relationship with HR. We suggest that males have greater energetic and evolutionary incentives to expand their HR with increasing BM, and more physical capacity to do so. Traditional studies on HR scaling that disregard individual sex may, in reality, reflect an average of two distinct patterns, while failing to accurately represent either one.

Tidal dynamics in a quasi-rectangular semi-enclosed basin with a constriction at its flank - Juan Torres-Córdoba; Arnoldo Valle-Levinson; Vladimir G. Toro-Valencia; Yuley Cardona; Juan F. Paniagua-Arroyave; Maria C. Aguirre-Pérez (Estuarine, Coastal and Shelf Science, 2025)

Effects of prolonged unsaturated fatty acid supplementation on reproductive competence and metabolic profiles in serum and follicular fluid of Holstein heifers - Lenita C. Verdurico; Caio S. Takiya; Alanne T. Nunes; Tiago A. Del Valle; Filipe Zanferari; Rodrigo Gardinal; Gustavo D. Calomeni; Elmeson Ferreira de Jesus; Guilherme G. Silva; Larissa Vitória Franco da Cruz; Francisco P. Rennó (Animal Reproduction Science, 2025)

Semi-enclosed coastal systems of South America: compilation and dynamic-based classification - Óscar Álvarez-Silva; Juan F. Paniagua-Arroyave; Edgar Cantero; Guilherme C. Lessa; Diego Moreira; Lauren Ross; Pablo Santoro; Carlos A.F. Schettini; Megan E. Williams; Arnoldo Valle-Levinson (Continental Shelf Research, 2025)

Biomass waste as a raw material for the mesoporous catalyst synthesis and its application in HDO of guaiacol for biofuel production - Lorena P. Rivoira; Brenda C. Ledesma; María V. Fraire; Verónica A. Valles; Marcos B. Gómez Costa; Andrea R. Beltramone (Clean Technologies and Environmental Policy, 2025)

Use of Hansen solubility parameters to select supercritical carbon dioxide cosolvents for improved extraction selectivity: Case study on green tea decaffeination - José M. del Valle; Laura Cuellar; Roberto Canales; Juan C. de la Fuente; Gonzalo A. Núñez (Journal of Food Engineering, 2025)

COVID-19 pandemic exacerbated food insecurity in South American countries - Carlos Frederico A. Vasconcelos-Neto; Michelle Jacob; Daniel Tregidgo; Denis Valle; Hani R. El Bizri; Sávio Marcelino Gomes; Julia E. Fa; Thais Q. Morcatty; Frederico Ozanan Barros Monteiro; Alessandra Scofield; Alessandra Matte; Willandia A. Chaves; et al. (Food Security, 2025)
The COVID-19 pandemic triggered unparalleled political, economic, and social ramifications, exacerbating global food insecurity (FI). To understand the overall impact of the pandemic and how different socio-economic groups were affected, we assessed prevalence and severity of FI in a sample of 18,997 households across seven countries in South America. We employed the Food Insecurity Experience Scale developed by the FAO. Our results showed that pre-pandemic, 4.5% of the sampled population across the entire continent faced Moderate FI, while 0.6% experienced severe FI. During the pandemic, Moderate FI increased to 16.9% (+ 12.4%), and Severe FI to 2.7% (+ 2.1%). By country, pre-pandemic households in Venezuela had the highest prevalence of Moderate FI (9.7%), with Peru experiencing the highest Severe FI frequency (1.1%). Peru had the greatest rise in Moderate (+ 23.9%) and Severe FI (+ 4.6%) during the pandemic. Low-income households, defined as those earning < 2 minimum wages per month, were most susceptible to FI. Uruguayan low-income families exhibited the most significant rise (+ 40.4%) in Moderate FI, while those in Peru experienced an increase of + 9.1% in Severe FI. This study measures the profound and far-reaching impact of the COVID-19 pandemic on FI in South America. Our findings also emphasise the critical importance of implementing effective public policy interventions to improve resilience against future shocks. This would enable policymakers to develop targeted strategies that address the immediate challenges posed by pandemics as well as laying the groundwork for a more resilient and sustainable food security landscape in the region.

Anoxic desulfurization of biogas rich in hydrogen sulfide through feedback control using biotrickling filters: Operational limits and multi-omics analysis - J. Brito; C. Frade-González; F. Almenglo; J.J. González-Cortés; A. Valle; M.C. Durán-Ruiz; M. Ramírez (Bioresource Technology, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Corrigendum to “The FLUKA Monte Carlo simulation of the magnetic spectrometer of the FOOT experiment” [Computer physics communications, Volume 307, (2025) 109398] - Y. Dong; S.M. Valle; G. Battistoni; I. Mattei; C. Finck; V. Patera; A. Alexandrov; B. Alpat; G. Ambrosi; S. Argiro; M. Barbanera; N. Bartosik; et al. (Computer Physics Communications, 2025)

The FLUKA Monte Carlo simulation of the magnetic spectrometer of the FOOT experiment - Y. Dong; S.M. Valle; G. Battistoni; I. Mattei; C. Finck; V. Patera; A. Alexandrov; B. Alpat; G. Ambrosi; S. Argirò; M. Barbanera; N. Bartosik; et al. (Computer Physics Communications, 2025)

DiverReef : A global database of the behavior of recreational divers and their interactions with reefs over 20 years - Vinicius J. Giglio; Johnatas Adelir‐Alves; Natalia Balzaretti Merino; Myrna Leticia Bravo‐Olivas; Emma F. Camp; Edoardo Casoli; Rosa Maria Chávez‐Dagostino; Eliana Ferretti; Douglas Fraser; Ana C. Grillo; Santiago Jiménez‐Guiérrez; Kelen L. Leite; et al. (Ecology, 2025)
Recreational diving is an important activity in reef environments worldwide, providing income and employment for coastal communities and connecting visiting divers to these ecosystems promoting conservation and stewardship. However, if poorly managed, diving has the potential to cause detrimental effects on benthic communities via mechanical damage caused by physical contact of divers with the reef, often in the form of unintentional fin kicks resulting from poor buoyancy. Understanding diver–reef interaction patterns is important to elucidate the potential impacts of diving tourism on the reef biota. The DiverReef database provides the first public dataset on the underwater behavior of recreational divers in shallow reef environments (

Imagine, Discover, Inspire: Proceedings of the 4th International Conference of the Trisomy 21 Research Society - Lisi Flores-Aguilar; Eric D. Hamlett; Paula Araya; Eugenio Barone; Anita Bhattacharyya; Maria Carmona-Iragui; Li Chan; Brad Christian; Alberto C. S. Costa; Floriana Costanzo; Laura Del Hoyo Soriano; Mara Dierssen; et al. (NeuroMolecular Medicine, 2025)
Down syndrome (DS) or trisomy 21 (T21) is present in a significant number of children and adults around the world and is associated with cognitive and medical challenges. Through research, the T21 Research Society (T21RS), established in 2014, unites a worldwide community dedicated to understanding the impact of T21 on biological systems and improving the quality of life of people with DS across the lifespan. T21RS hosts an international conference every two years to support collaboration, dissemination, and information sharing for this goal. In 2022, T21RS hosted an international conference in Long Beach, California, from June 9 to 12. The conference, attended by 483 people including scientists, families, self-advocates, and industry representatives from 17 countries, was a dynamic and interactive meeting that shared discoveries from international research teams. This summary highlights the scientific discoveries shared at the 4th T21RS meeting with the Imagine, Discover, Inspire theme.

Calcium oxide reduces fermentation losses and improves the nutritional value of brewery-spent grain silage - Jozivaldo P.G. de Morais; Laura Hartung; Marjorye A. Nunes; Paulo D. Sobires; Fabiellen C. Pereira; Mauro E. Vargas; Tiago A. Del Valle; Mariana Campana (Animal Feed Science and Technology, 2025)

Heat domes increase vulnerability of native stingless bees by simultaneously weakening key survival traits - J.J.G. Quezada-Euán; R.G. Medina; A. Soto-Correa; C. Pech-Jiménez; R.J. Paxton; T. Solís; R. Aragón-Pech; H. Moo-Valle (Science of The Total Environment, 2024)

Toxicity of crude oil-derived polar unresolved complex mixtures to Pacific herring embryos: Insights beyond polycyclic aromatic hydrocarbons - Maxwell L. Harsha; Yanila Salas-Ortiz; Alysha D. Cypher; Ed Osborn; Eduardo Turcios Valle; Jacob L. Gregg; Paul K. Hershberger; Yuri Kurerov; Sarah King; Aleksandar I. Goranov; Patrick G. Hatcher; Anastasia Konefal; et al. (Science of The Total Environment, 2024)

A Transcriptomic Comparative Study of Cranial Vasculature - Jianing Zhang; Jee-Yeon Ryu; Selena-Rae Tirado; Lawrence D. Dickinson; Aviva Abosch; M. Ali Aziz-Sultan; Alan S. Boulos; Daniel L. Barrow; H. Hunt Batjer; Tamar R. Binyamin; Spiros L. Blackburn; Edward F. Chang; et al. (Translational Stroke Research, 2024)

The importance of locally sourced data in identifying population trends: Insights from Iberian vertebrates - Roberto C. Rodríguez-Caro; Zebensui Morales-Reyes; Alba Aguión; Rebeca Arias-Real; Eneko Arrondo; Eneko Aspillaga; Jordi Boada; Andrea Campos-Candela; Mónica Expósito-Granados; Aitor Forcada; Robin Freeman; Miguel Ángel Gómez-Serrano; et al. (Biological Conservation, 2024)

Effect of toluene on siloxane biodegradation and microbial communities in biofilters - J.J. González-Cortés; P.A. Lamprea-Pineda; A. Valle; M. Ramírez; H. Van Langenhove; K. Demeestere; C. Walgraeve (Waste Management, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Post-mortem detection of hemoplasmas (hemotropic Mycoplasma spp.) in South American fur seal (Arctocephalus australis) sampled in Rio Grande do Sul State, southern Brazil - Luciano de Oliveira Battisti; Anna Claudia Baumel Mongruel; Renata Fagundes-Moreira; Vinícius Baggio-Souza; Viviane Kelin de Souza; Derek Blaese de Amorim; Paulo Guilherme C. Wagner; Ugo A. Souza; Ana Paula Gonçalves; Aline Girotto-Soares; Stella de Faria Valle; Marcos Rogério André; et al. (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Identification of trends in the Tancítaro-Parícutin seismic swarm sequence through fractal characteristics of inter-event times - A. T. Mendoza-Rosas; C. A. Juárez-Valle; A. Figueroa-Soto; P. Corona-Chávez; D. A. Gómez-Calderón; A. Mendoza-Ponce (Journal of Seismology, 2024)

Comparative MRI analysis of the forebrain of three sauropsida models - S Jiménez; I Santos-Álvarez; E Fernández-Valle; D Castejón; P Villa-Valverde; C Rojo-Salvador; P Pérez-Llorens; M. J. Ruiz-Fernández; S. Ariza-Pastrana; R. Martín-Orti; Juncal González-Soriano; Nerea Moreno (Brain Structure and Function, 2024)
The study of the brain by magnetic resonance imaging (MRI) allows to obtain detailed anatomical images, useful to describe specific encephalic structures and to analyze possible variabilities. It is widely used in clinical practice and is becoming increasingly used in veterinary medicine, even in exotic animals; however, despite its potential, its use in comparative neuroanatomy studies is still incipient. It is a technology that in recent years has significantly improved anatomical resolution, together with the fact that it is non-invasive and allows for systematic comparative analysis. All this makes it particularly interesting and useful in evolutionary neuroscience studies, since it allows for the analysis and comparison of brains of rare or otherwise inaccessible species. In the present study, we have analyzed the prosencephalon of three representative sauropsid species, the turtle Trachemys scripta (order Testudine), the lizard Pogona vitticeps (order Squamata) and the snake Python regius (order Squamata) by MRI. In addition, we used MRI sections to analyze the total brain volume and ventricular system of these species, employing volumetric and chemometric analyses together. The raw MRI data of the sauropsida models analyzed in the present study are available for viewing and downloading and have allowed us to produce an atlas of the forebrain of each of the species analyzed, with the main brain regions. In addition, our volumetric data showed that the three groups presented clear differences in terms of total and ventricular brain volumes, particularly the turtles, which in all cases presented distinctive characteristics compared to the lizards and snakes.

Human plasmacytoid dendritic cells express the functional purinergic halo (CD39/CD73) - S. A. Sosa-Luis; W. J. Ríos-Ríos; A. Almaraz-Arreortua; M. A. Romero-Tlalolini; S. R. Aguilar-Ruiz; R. Valle-Ríos; C. Sánchez-Torres; H. Torres-Aguilar (Purinergic Signalling, 2024)

Inclusive simulation game development to enhance Florida research and management: Cedar Key oyster fishery - Chad R. Palmer; Denis Valle; Edward V. Camp; Wendy-Lin Bartels; Martha C. Monroe (Environmental Modelling & Software, 2024)

Antimicrobial Resistance Profiles of Multidrug-Resistant Enterobacteria Isolated from Feces of Weaned Piglets - Marlon do Valle Barroso; Juliana Soares da Silva; Sofia Magalhães Moreira; Yasmin Neves Vieira Sabino; Gabriel Cipriano Rocha; Maria Aparecida Scatamburlo Moreira; Denise Mara Soares Bazzolli; Hilario C. Mantovani (Current Microbiology, 2024)

Upcycling spent coffee grounds and waste PET bottles into electrospun composite nanofiber mats for oil structuring applications - J.F. Rubio-Valle; C. Valencia; M.C. Sánchez; J.E. Martín-Alfonso; J.M. Franco (Resources, Conservation and Recycling, 2023)

Maximum electrodeposition capacity of Pb on a stainless-steel cathode using a galvanostatic regime - J. C. Rojas-Montes; V. J. Martínez-Gómez; J. C. Fuentes-Aceituno; S. Valle-Cervantes; B. P. Gómez-Lozano; L. R. Quiñones-Rosales (International Journal of Environmental Science and Technology, 2023)

Using NIR irradiation and magnetic bismuth ferrite microparticles to accelerate the removal of polystyrene microparticles from the drinking water - J. Oliva; L.S. Valle-Garcia; L. Garces; A.I. Oliva; E. Valadez-Renteria; D.A. Hernandez-Bustos; J.J. Campos-Amador; C. Gomez-Solis (Journal of Environmental Management, 2023)

Threatened conservation scientists: The aftermath of an eye-opening publication on rewilding - María de las Mercedes Guerisoli; Mauro I. Schiaffini; Pablo Teta; Alejandro E.J. Valenzuela; Patricia Mirol; Javier Nori; Guillermo E. Defossé; María Marcela Godoy; Pablo Krieger; Tomás Withington; María G. Agostini; Christopher B. Anderson; et al. (Biological Conservation, 2023)

MicroRNA signature from extracellular vesicles of HCV/HIV co-infected individuals differs from HCV mono-infected - Victoria Cairoli; Daniel Valle-Millares; María C. Terrón-Orellano; Daniel Luque; Pablo Ryan; Lourdes Dominguez; Luz Martín-Carbonero; Ignacio De los Santos; Elena De Matteo; Beatriz Ameigeiras; Verónica Briz; Paola Casciato; et al. (Journal of Molecular Medicine, 2023)
Hepatitis C virus (HCV) coinfection with human immunodeficiency virus (HIV) has a detrimental impact on disease progression. Increasing evidence points to extracellular vesicles (EVs) as important players of the host-viral cross-talk. The microRNAs (miRNAs), as essential components of EVs cargo, are key regulators of normal cellular processes and also promote viral replication, viral pathogenesis, and disease progression. We aimed to characterize the plasma-derived EVs miRNA signature of chronic HCV infected and HIV coinfected patients to unravel the molecular mechanisms of coinfection. EVs were purified and characterized from 50 plasma samples (21 HCV mono- and 29 HCV/HIV co-infected). EV-derived small RNAs were isolated and analyzed by massive sequencing. Known and de novo miRNAs were identified with miRDeep2. Significant differentially expressed (SDE) miRNA identification was performed with generalized linear models and their putative dysregulated biological pathways were evaluated. Study groups were similar for most clinical and epidemiological characteristics. No differences were observed in EVs size or concentration between groups. Therefore, HCV/HIV co-infection condition did not affect the concentration or size of EVs but produced a disturbance in plasma-derived EVs miRNA cargo. Thus, a total of 149 miRNAs were identified (143 known and 6 de novo) leading to 37 SDE miRNAs of which 15 were upregulated and 22 downregulated in HCV/HIV co-infected patients. SDE miRNAs regulate genes involved in inflammation, fibrosis, and cancer, modulating different biological pathways related to HCV and HIV pathogenesis. These findings may help to develop new generation biomarkers and treatment strategies, in addition to elucidate the mechanisms underlying virus–host interaction. Key messages HCV and HCV/HIV displayed similar plasma-EV size and concentration. EVs- derived miRNA profile was characterized by NGS. 37 SDE miRNAs between HCV and HCV/HIV were observed. SDE miRNAs regulate genes involved in inflammation, fibrosis and cancer.

Amber and the Cretaceous Resinous Interval - Xavier Delclòs; Enrique Peñalver; Eduardo Barrón; David Peris; David A. Grimaldi; Michael Holz; Conrad C. Labandeira; Erin E. Saupe; Christopher R. Scotese; Mónica M. Solórzano-Kraemer; Sergio Álvarez-Parra; Antonio Arillo; et al. (Earth-Science Reviews, 2023)

Multiplicative processing in the modeling of cognitive activities in large neural networks - Juan C. Valle-Lisboa; Andrés Pomi; Eduardo Mizraji (Biophysical Reviews, 2023)
Explaining the foundation of cognitive abilities in the processing of information by neural systems has been in the beginnings of biophysics since McCulloch and Pitts pioneered work within the biophysics school of Chicago in the 1940s and the interdisciplinary cybernetists meetings in the 1950s, inseparable from the birth of computing and artificial intelligence. Since then, neural network models have traveled a long path, both in the biophysical and the computational disciplines. The biological, neurocomputational aspect reached its representational maturity with the Distributed Associative Memory models developed in the early 70 s. In this framework, the inclusion of signal-signal multiplication within neural network models was presented as a necessity to provide matrix associative memories with adaptive, context-sensitive associations, while greatly enhancing their computational capabilities. In this review, we show that several of the most successful neural network models use a form of multiplication of signals. We present several classical models that included such kind of multiplication and the computational reasons for the inclusion. We then turn to the different proposals about the possible biophysical implementation that underlies these computational capacities. We pinpoint the important ideas put forth by different theoretical models using a tensor product representation and show that these models endow memories with the context-dependent adaptive capabilities necessary to allow for evolutionary adaptation to changing and unpredictable environments. Finally, we show how the powerful abilities of contemporary computationally deep-learning models, inspired in neural networks, also depend on multiplications, and discuss some perspectives in view of the wide panorama unfolded. The computational relevance of multiplications calls for the development of new avenues of research that uncover the mechanisms our nervous system uses to achieve multiplication.

Diversity and seasonal variation of the molluscan community associated with the seagrass Halodule wrightii in a marine protected area in the southern Gulf of California - C. J. Pérez-Estrada; R. Rodríguez-Estrella; F. G. Brun-Murillo; P. Gurgo-Salice; R. Valles-Jiménez; E. Morales-Bojórquez; M. A. Medina-López (Aquatic Ecology, 2023)

60 Bite and mouth shape variations assessment during different slow-feeding management in ponies: A geometric morphometric evaluation - C. Bordin; F. Raspa; P.A. Harris; A. Ellis; A. Roggero; C. Palestrini; D. Bergero; E. Valle (Journal of Equine Veterinary Science, 2023)

Role of PumB antitoxin as a transcriptional regulator of the PumAB type-II toxin–antitoxin system and its endoribonuclease activity on the PumA (toxin) transcript - K. C. Hernández-Ramírez; M. I. Valle-Maldonado; J. A. Patiño-Medina; S. Calo; I. E. Jácome-Galarza; V. Garre; V. Meza-Carmen; M. I. Ramírez-Díaz (Molecular Genetics and Genomics, 2023)

Biological characterization of bristle extract of Lonomia descimoni caterpillar (Lepidoptera, Saturniidae) and effectiveness of Lonomia antivenom to neutralize experimental envenomation in rats - Isabelle Valle dos Anjos; Camila Gonzalez; Juana Diaz; Juliana Mozer Sciani; Ida S. Sano-Martins; Luís Roberto C. Gonçalves (Toxicon, 2023)

Microglial NLRP3 Inflammasome Induces Excitatory Synaptic Loss Through IL-1β-Enriched Microvesicle Release: Implications for Sepsis-Associated Encephalopathy - Carolina A. Moraes; Eugenio D. Hottz; Débora Dos Santos Ornellas; Daniel Adesse; Carolina T. de Azevedo; Joana C. d’Avila; Camila Zaverucha-do-Valle; Tatiana Maron-Gutierrez; Helene Santos Barbosa; Patricia Torres Bozza; Fernando Augusto Bozza (Molecular Neurobiology, 2023)

Modulation of inspiratory burst duration and frequency by bombesin in vitro - Consuelo Morgado-Valle; Jeffrey C. Smith; Juan Fernandez-Ruiz; Leonor Lopez-Meraz; Luis Beltran-Parrazal (Pflügers Archiv - European Journal of Physiology, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Kelp Forest Drag Coefficients Derived from Tidal Flow Data - Stephen Monismith; Maha Alnajjar; Margaret Daly; Arnoldo Valle-Levinson; Braulio Juarez; Matheus Fagundes; Tom Bell; C. Brock Woodson (Estuaries and Coasts, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Copper(II) and lead(II) adsorption onto zinc sulfide nanoparticles effects of light, pH, time, temperature, and interferences - J. M. Cantu; J. P. Valle; A. Puente; C. Valdes; K. Flores; H. M. Morales; E. Fletes; M. Alcoutlabi; E. Kotsikorou; J. G. Parsons (International Journal of Environmental Science and Technology, 2022)

Diet composition and feeding habits of the crocodile shark, Pseudocarcharias kamoharai - Marcos D. Calle-Morán; Ana R. Hernández-Téllez; Evelyn R. Tibán-Vivar; Yari E. Intriago-Vera; Israel G. Del Valle-Coello; Beatriz C. Loor-Jama; Ángel R. Ganchozo-López (Environmental Biology of Fishes, 2022)

Basidiocarp structures of Lentinus crinitus: an antimicrobial source against foodborne pathogens and food spoilage microorganisms - Míria Benetati Delgado Bertéli; Mariana Martins Magalhães de Souza; Lillian Barros; Isabel C. F. R. Ferreira; Jasmina Glamočlija; Marina Soković; Douglas Cardoso Dragunski; Juliana Silveira do Valle; Ederlan de Souza Ferreira; Laise Cedraz Pinto; Carolina Oliveira de Souza; Suelen Pereira Ruiz; et al. (World Journal of Microbiology and Biotechnology, 2022)

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Identifying Pathways for Climate-Resilient Multispecies Fisheries - Kendra A. Karr; Valerie Miller; Eva Coronado; Nadia C. Olivares-Bañuelos; Martha Rosales; Javier Naretto; Luciano Hiriart-Bertrand; Camila Vargas-Fernández; Romina Alzugaray; Rafael Puga; Servando Valle; L. P. Osman; et al. (Frontiers in Marine Science, 2021)
Fish live in communities, and most fisheries catch multiple species, yet fishery management predominately focuses on single species. In many multispecies fisheries, a variety of species are generally caught together at similar rates. Failure to account for this adequately in management has resulted in serial depletion and alterations to the ecosystem. Ideally, multispecies fisheries management should strive to produce good yields from specific valuable stocks and avoid adverse impacts of fishing on marine ecosystems. Moreover, multispecies management should aim to build resilience to changes in stock productivity and distribution driven by climate change. Here, we present tools and pathways that seven fisheries are adopting to achieve these goals. These case studies – from Mexico, Cuba, and Chile – differ in data richness, governance structure, and management resources. The management systems are also in various stages of evolution from unmanaged to complete management of a single species but transitioning to multispecies management. While various analytical tools and decision-making processes are described in the case studies, a common feature is the use of participatory stakeholder processes to build capacity and socialize the importance of multispecies management. We use lessons from these cases to recommend a multispecies management approach to overcome the limitations of current practices (typically single-species catch limits or large spatial restrictions), using the participatory processes and data-limited assessments to create stock complexes that simplify multispecies management (i.e., the “fish baskets” approach). Indicator species for each fish basket are identified to support the development of fishery performance indicators, reference values, harvest control rules, and management measures to create an adaptive management cycle to enhance the fishery’s resilience to impacts induced by climate change and other factors.

IFIH1 loss-of-function variants contribute to very early-onset inflammatory bowel disease - Mara Cananzi; Elizabeth Wohler; Antonio Marzollo; Davide Colavito; Jing You; Huie Jing; Silvia Bresolin; Paola Gaio; Renan Martin; Claudia Mescoli; Sangeeta Bade; Jennifer E. Posey; et al. (Human Genetics, 2021)

Temporal dynamic and economic valuation of recreational fisheries of the lower Cuiabá River, Brazilian Pantanal - Brayan Allan R. Massaroli; Joisiane Mendes Araújo; Jean C. G. Ortega; André Valle Nunes; Lúcia Mateus; Samuel Elias Silva; Jerry Penha (Fisheries Management and Ecology, 2021)
Fisheries are the most common ecosystem service that fish provide to human populations, yet recreational fisheries are often overlooked when evaluating such services. Here, the socioeconomic profiles of fishers, the composition of their catches and catch per unit effort (CPUE) are described, to estimate the economic value of the recreational fishery on a stretch of the Cuiabá River in the Brazilian Pantanal. Questionnaires were used to obtain socioeconomic information and fishing yield from fishers for 2013 and 2014. Additionally, a census on the number of fishers and fishing platforms along the sampled region was conducted in 2018. This recreational fishery mostly involves middle class adult males, based mostly in the Cuiabá city metropolitan region. They invested, on average, US$41.1 (SD = US$16.5, median = $35.2) per fishing visit, catching around 19 fish species. Overall, mean CPUE from the recreational fishery was 42.20 fish/fisher.day (17.4 kg/fisher/day). Annual economic value of this recreational fishery was estimated at around US$1.8 million, which highlights the importance of this activity to the local economy. Greater environmental conservation efforts are recommend to ensure the long‐term viability of this ecosystem service.

Vanishing permanent glaciers: climate change is threatening a European Union habitat (Code 8340) and its poorly known biodiversity - M. Gobbi; R. Ambrosini; C. Casarotto; G. Diolaiuti; G. F. Ficetola; V. Lencioni; R. Seppi; C. Smiraglia; D. Tampucci; B. Valle; M. Caccianiga (Biodiversity and Conservation, 2021)

Facile fabrication of hybrid titanium(IV) isopropoxide/pozzolan nanosheets (TnS-Pz) of high photocatalytic activity: characterization and application for Cr(VI) reduction in an aqueous solution - Aline M. Novack; Glaydson S. dos Reis; Fabíola V. Hackbarth; Belisa A. Marinho; Maja B. Ðolić; José A. B. Valle; Carlos H. Sampaio; Eder C. Lima; Guillherme L. Dotto; Antônio Augusto Ulson de Souza; Vítor J. P. Vilar; Selene M. A. Guelli Ulson de Souza (Environmental Science and Pollution Research, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Involvement of adenosine A1 and A2A receptors on guanosine-mediated anti-tremor effects in reserpinized mice - C. M. Massari; L. C. Constantino; N. F. Marques; L. B. Binder; M. Valle-León; M. López-Cano; V. Fernández-Dueñas; F. Ciruela; C. I. Tasca (Purinergic Signalling, 2020)

Virulence Conferred by PumA Toxin from the Plasmid-Encoded PumAB Toxin-Antitoxin System is Regulated by Quorum System - Karen C. Hernández-Ramírez; Brenda Valerio-Arellano; Marco I. Valle-Maldonado; León F. Ruíz-Herrera; Victor Meza-Carmen; Martha I. Ramírez-Díaz (Current Microbiology, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Correction to: Ecological restoration as a strategy for mitigating and adapting to climate change: lessons and challenges from Brazil - Mercedes M. C. Bustamante; José Salomão Silva; Aldicir Scariot; Alexandre Bonesso Sampaio; Daniel Luis Mascia Vieira; Edenise Garcia; Edson Sano; Geraldo Wilson Fernandes; Giselda Durigan; Iris Roitman; Isabel Figueiredo; Ricardo Ribeiro Rodrigues; et al. (Mitigation and Adaptation Strategies for Global Change, 2020)

GISH-based comparative genomic analysis in Urochloa P. Beauv. - Caio T. R. Corrêa; Nathalia G. Z. Bonetti; Sanzio C. L. Barrios; Cacilda B. do Valle; Giovana A. Torres; Vânia H. Techio (Molecular Biology Reports, 2020)

Lanthanum- and cerium-based functionalization of chars and activated carbons for the adsorption of fluoride and arsenic ions - E. E. Merodio-Morales; H. E. Reynel-Ávila; D. I. Mendoza-Castillo; C. J. Duran-Valle; A. Bonilla-Petriciolet (International Journal of Environmental Science and Technology, 2020)

Ecological restoration as a strategy for mitigating and adapting to climate change: lessons and challenges from Brazil - Mercedes M. C. Bustamante; José Salomão Silva; Aldicir Scariot; Alexandre Bonesso Sampaio; Daniel Luis Mascia; Edenise Garcia; Edson Sano; Geraldo Wilson Fernandes; Giselda Durigan; Iris Roitman; Isabel Figueiredo; Ricardo Ribeiro Rodrigues; et al. (Mitigation and Adaptation Strategies for Global Change, 2019)

Validation of a universal set of primers to study animal‐associated microeukaryotic communities - Javier del Campo; Maria J. Pons; Maria Herranz; Kevin C. Wakeman; Juana del Valle; Mark J. A. Vermeij; Brian S. Leander; Patrick J. Keeling (Environmental Microbiology, 2019)
Summary The application of metabarcoding to study animal‐associated microeukaryotes has been restricted because the universal barcode used to study microeukaryotic ecology and distribution in the environment, the Small Subunit of the Ribosomal RNA gene (18S rRNA), is also present in the host. As a result, when host‐associated microbial eukaryotes are analysed by metabarcoding, the reads tend to be dominated by host sequences. We have done an in silico validation against the SILVA 18S rRNA database of a non‐metazoan primer set (primers that are biased against the metazoan 18S rRNA) that recovers only 2.6% of all the metazoan sequences, while recovering most of the other eukaryotes (80.4%). Among metazoans, the non‐metazoan primers are predicted to amplify 74% of Porifera sequences, 4% of Ctenophora, and 15% of Cnidaria, while amplifying almost no sequences within Bilateria. In vivo , these non‐metazoan primers reduce significantly the animal signal from coral and human samples, and when compared against universal primers provide at worst a 2‐fold decrease in the number of metazoan reads and at best a 2800‐fold decrease. This easy, inexpensive, and near‐universal method for the study of animal‐associated microeukaryotes diversity will contribute to a better understanding of the microbiome.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

PTPN22 +788 G>A (R263Q) Polymorphism is Associated with mRNA Expression but it is not a Susceptibility Marker for Rheumatoid Arthritis Patients from Western Mexico - S. Ramírez-Pérez; G. A. Sánchez-Zuno; L. E. Chavarría-Buenrostro; M. Montoya-Buelna; I. V. Reyes-Pérez; M. G. Ramírez-Dueñas; C. A. Palafox-Sánchez; G. E. Martínez-Bonilla; J. F. Muñoz-Valle (Biochemical Genetics, 2019)

Glyphosate detection: methods, needs and challenges - A. L. Valle; F. C. C. Mello; R. P. Alves-Balvedi; L. P. Rodrigues; L. R. Goulart (Environmental Chemistry Letters, 2019)

Ayahuasca improves emotion dysregulation in a community sample and in individuals with borderline-like traits - Elisabet Domínguez-Clavé; Joaquim Soler; Juan C. Pascual; Matilde Elices; Alba Franquesa; Marta Valle; Enric Alvarez; Jordi Riba (Psychopharmacology, 2019)

Serum P-glycoprotein level: a potential biomarker of DMARD failure in patients with rheumatoid arthritis - E. E. Perez-Guerrero; L. Gonzalez-Lopez; J. F. Muñoz-Valle; J. C. Vasquez-Jimenez; M. Ramirez-Villafaña; E. N. Sanchez-Rodriguez; S. R. Gutierrez-Ureña; S. Cerpa-Cruz; E. A. Aguilar-Chavez; E. G. Cardona-Muñoz; M. L. Vazquez-Villegas; A. M. Saldaña-Cruz; et al. (Inflammopharmacology, 2018)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Rare Risk Variants Identification by Identity-by-Descent Mapping and Whole-Exome Sequencing Implicates Neuronal Development Pathways in Schizophrenia and Bipolar Disorder - C. Salvoro; S. Bortoluzzi; A. Coppe; G. Valle; E. Feltrin; M. L. Mostacciuolo; G. Vazza (Molecular Neurobiology, 2018)

Comparative chromosome painting in Columbidae (Columbiformes) reinforces divergence in Passerea and Columbea - Rafael Kretschmer; Ivanete de Oliveira Furo; Ricardo José Gunski; Analía del Valle Garnero; Jorge C. Pereira; Patricia C. M. O’Brien; Malcolm A. Ferguson-Smith; Edivaldo Herculano Corrêa de Oliveira; Thales Renato Ochotorena de Freitas (Chromosome Research, 2018)

Discovery of a novel iflavirus sequence in the eastern paralysis tick Ixodes holocyclus - Caitlin A. O’Brien; Sonja Hall-Mendelin; Jody Hobson-Peters; Georgia Deliyannis; Andy Allen; Ala Lew-Tabor; Manuel Rodriguez-Valle; Dayana Barker; Stephen C. Barker; Roy A. Hall (Archives of Virology, 2018)

Carotenoids in roots indicated the level of stress induced by mannitol and sodium azide treatment during the early stages of maize germination - Lázaro Hernández; Daviel Gómez; Bárbara Valle; Christoph C. Tebbe; Richard Trethowan; Rosa Acosta; Lourdes Yabor; José Carlos Lorenzo (Acta Physiologiae Plantarum, 2018)

Multiplexed lateral flow immunoassay to discriminate Solenopsis invicta, Solenopsis richteri, and Solenopsis invicta × richteri hybrids - S. M. Valles; C. A. Strong; A.-M. A. Callcott (Insectes Sociaux, 2018)

Sonar technology and underwater imagery analysis can enhance invasive Dreissena distribution assessment in large rivers - K. Mehler; L. E. Burlakova; A. Y. Karatayev; Z. Biesinger; A. Valle-Levinson; C. Castiglione; D. Gorsky (Hydrobiologia, 2018)

Are carcass and meat quality of male dual-purpose chickens competitive compared to slow-growing broilers reared under a welfare-enhanced organic system? - Philipp C. Muth; Shahin Ghaziani; Iris Klaiber; Anne Valle Zárate (Organic Agriculture, 2018)

Temporary immersion bioreactors (TIB) provide a versatile, cost-effective and reproducible in vitro analysis of the response of pineapple shoots to salinity and drought - Daviel Gómez; Lázaro Hernández; Bárbara Valle; Julia Martínez; Mariela Cid; Maritza Escalona; Martha Hernández; Gerrit T. S. Beemster; Christoph C. Tebbe; Lourdes Yabor; José Carlos Lorenzo (Acta Physiologiae Plantarum, 2017)

In vivo and in vitro studies using larval and adult antigens from Neobenedenia melleni on immune response in yellowtail ( Seriola lalandi ) - M Reyes‐Becerril; E Alamillo; A Trasviña; I Hirono; H Kondo; W Jirapongpairoj; F Ascencio‐Valle; C Angulo (Journal of Fish Diseases, 2017)
Neobenedenia melleni is a monogenean parasite that causes significant mortality and economic losses in fish aquaculture. Changes in the antigenic composition of this parasite occur during its developmental stages. In this study, we evaluated humoral parameters in serum and transcriptional immune responses of yellowtail naturally infected with N. melleni . In addition, in vitro assays were performed to study the stimulatory effects of antigens from larvae and adults on spleen leucocytes from non‐infected fish at 6 and 24 h post‐stimulation. The results showed enhanced total protein, myeloperoxidase and antiprotease activities in N. melleni ‐infected fish compared with non‐infected ones. The induction of Toll‐like receptors (TLRs) and pro‐inflammatory cytokines in spleen leucocytes during natural infection with N. melleni suggests that these immune‐related genes play an important role in the initiation of the immune defence mechanism for controlling parasite infection. Interestingly, the magnitude of in vitro responses of spleen leucocytes was dependent on the parasitic stage. An important stimulation of gene expression by adult antigens on spleen leucocytes was observed. Differential expression patterns of TLRs and target cytokines in yellowtail leucocytes in both in vivo and in vitro studies suggest that the quality of yellowtail immune response is conditioned by N. melleni development.

Sow efficiency and early piglet mortality in two local pig breeds on smallholder farms in northern Vietnam—a longitudinal study - Philipp C. Muth; Le T. T. Huyen; Anne Valle Zárate (Tropical Animal Health and Production, 2017)

Introduced marine macroflora of Lebanon and its distribution on the Levantine coast - G. BITAR; A. A. RAMOS-ESPLÁ; O. OCAÑA; Y. R. SGHAIER; A. FORCADA; C. VALLE; H. EL SHAER; M. VERLAQUE (Mediterranean Marine Science, 2017)
The marine macroflora introduced into Lebanon was studied through an analysis of historical data and field studies carried out since 1991. A total of 29 introduced species have been listed: 3 Chromobionta, 13 Rhodobionta, 12 Chlorobionta and 1 Streptobionta. Among them, Caulerpa taxifolia var. distichophylla, Spatoglossum variabile and Womersleyella setacea are recorded for the first time from Lebanon. Among them, Asparagopsis taxiformis, C. taxifolia var. distichophylla, Cladophora patentiramea, Codium arabicum, Codium parvulum, Galaxaura rugosa, Halophila stipulacea, Hypnea cornuta, Laurencia cf. chondrioides, Lophocladia lallemandii, Stypopodium schimperi, Ulva lactuca and Womersleyella setacea are potentially invasive species, and several of them already occupy extensive stretches of the Lebanese coast. The distribution of species on the Levantine coast, their dynamics and the current status of their populations are discussed.

Wave and tidal flushing in a near-equatorial mesotidal atoll - Mirella B. Costa; Eduardo C. Macedo; Arnoldo Valle-Levinson; Eduardo Siegle (Coral Reefs, 2017)

Differential expression and localization of Ankrd2 isoforms in human skeletal and cardiac muscles - Jovana Jasnic-Savovic; Sabine Krause; Slobodan Savic; Ana Kojic; Vlado Kovcic; Srdjan Boskovic; Aleksandra Nestorovic; Ljiljana Rakicevic; Olivia Schreiber-Katz; Johannes G. Vogel; Benedikt G. Schoser; Maggie C. Walter; et al. (Histochemistry and Cell Biology, 2016)

The third vegetative generation of a field-grown transgenic pineapple clone shows minor side effects of transformation on plant physiological parameters - Lourdes Yabor; Bárbara Valle; René Carlos Rodríguez; Carlos Aragón; Jutta Papenbrock; Christoph C. Tebbe; José Carlos Lorenzo (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Potential for the development of a marketing option for the specialty local Ban pork of a Thai ethnic smallholder cooperative group in Northwest Vietnam - Thi Thanh Huyen Le; Philipp C. Muth; André Markemann; Kerstin Schöll; Anne Valle Zárate (Tropical Animal Health and Production, 2016)

Intrachromosomal rearrangements in two representatives of the genus Saltator (Thraupidae, Passeriformes) and the occurrence of heteromorphic Z chromosomes - Michelly da Silva dos Santos; Rafael Kretschmer; Fabio Augusto Oliveira Silva; Mario Angel Ledesma; Patricia C. M. O’Brien; Malcolm A. Ferguson-Smith; Analía Del Valle Garnero; Edivaldo Herculano Corrêa de Oliveira; Ricardo José Gunski (Genetica, 2015)

Photoprotective and Antimutagenic Activity of Agaricus subrufescens Basidiocarp Extracts - M. C. D. da Costa; M. Regina; M. Cilião Filho; G. A. Linde; J. S. do Valle; L. D. Paccola-Meirelles; N. B. Colauto (Current Microbiology, 2015)

The 2013 Ibiza Calibration Campaign of Jason-2 and SARAL Altimeters - F. Frappart; N. Roussel; R. Biancale; J.J. Martinez Benjamin; F. Mercier; F. Perosanz; J. Garate Pasquin; J. Martin Davila; B. Perez Gomez; C. Gracia Gomez; R. Lopez Bravo; A. Tapia Gomez; et al. (Marine Geodesy, 2015)

Biochemical characteristics and modulation by external and internal factors of aminopeptidase-N activity in the hepatopancreas of a euryhaline burrowing crab - M. S. Michiels; J. C. del Valle; A. A. López Mañanes (Journal of Comparative Physiology B, 2015)

Microbial community diversity and physical–chemical features of the Southwestern Atlantic Ocean - Nelson Alves Junior; Pedro Milet Meirelles; Eidy de Oliveira Santos; Bas Dutilh; Genivaldo G. Z. Silva; Rodolfo Paranhos; Anderson S. Cabral; Carlos Rezende; Tetsuya Iida; Rodrigo L. de Moura; Ricardo Henrique Kruger; Renato C. Pereira; et al. (Archives of Microbiology, 2015)

Review of alien marine macrophytes in Tunisia - Y. R. SGHAIER; R. ZAKHAMA-SRAIEB; S. MOUELHI; M. VAZQUEZ; C. VALLE; A.A. RAMOS-ESPLA; J.M. ASTIER; M. VERLAQUE; F. CHARFI-CHEIKHROUHA (Mediterranean Marine Science, 2015)
In the present study, the list of alien marine macrophytes introduced into Tunisia was updated in the light of available data and new observations. A total of 27 alien marine macrophytes have been recorded so far from Tunisia: 18 Rhodophyta, 3 Ochrophyta, 5 Chlorophyta and 1 Magnoliophyta. For each species, the locality (-ies), the year (or) period and the source of the first observation in Tunisia are given. The distribution and the status (casual, cryptogenic, established or questionable) of species in Tunisia were evaluated and, where appropriate, discussed. Among them, Hypnea cornuta is reported for the first time from Tunisia. Fourteen alien marine macrophytes are established, whereas seven cryptogenic and two casual species require further investigation. Eleven species are considered as invasive or potentially invasive in the Mediterranean Sea: Acrothamnion preissii, Asparagopsis armata, A. taxiformis Indo-Pacific lineage, Hypnea cornuta, Lophocladia lallemandii, Womersleyella setacea, Caulerpa chemnitzia, C. cylindracea, C. taxifolia, Codium fragile subsp. fragile and Halophila stipulacea. Finally, the case of four questionable species is also discussed.

Electron affinity and dipole moment of 1,2,4,5-tetraoxanes antimalarials and correlation with activity against Plasmodium falciparum - Mariane C. de Paula; Marcelo S. Valle; Josefredo R. Pliego (Medicinal Chemistry Research, 2014)

Divergence in Expression of Candidate Genes for the Smoltification Process Between Juvenile Resident Rainbow and Anadromous Steelhead Trout - Benjamin C. Hecht; Madeline E. Valle; Frank P. Thrower; Krista M. Nichols (Marine Biotechnology, 2014)

Analytic Simulation of the Elastic Waves Propagation in the Neighborhood of Fluid Filled Wells with Monopole Sources - R. Ávila-Carrera; F. J. Sánchez-Sesma; James H. Spurlin; C. Valle-Molina; A. Rodríguez-Castellanos (Pure and Applied Geophysics, 2014)

Fear extinction and acute stress reactivity reveal a role of LPA1 receptor in regulating emotional-like behaviors - C. Pedraza; J. Sánchez-López; E. Castilla-Ortega; C. Rosell-Valle; E. Zambrana-Infantes; M. García-Fernández; F. Rodriguez de Fonseca; J. Chun; L. J. Santín; G. Estivill-Torrús (Brain Structure and Function, 2014)

Aerobiological and ecological study of the potentially allergenic ornamental plants in south Spain - M. J. Velasco-Jiménez; P. Alcázar; A. Valle; M. M. Trigo; F. Minero; E. Domínguez-Vilches; C. Galán (Aerobiologia, 2014)

Differential distribution of sperm subpopulations and incidence of pleiomorphisms in ejaculates of captive howling monkeys (Alouatta caraya) - R. R. Valle; F. M. Carvalho; J. A. P. C. Muniz; C. L. V. Leal; M. García-Herreros (The Science of Nature, 2013)

Cat-scratch disease in Northern Italy: atypical clinical manifestations in humans and prevalence of Bartonella infection in cats - E. Brunetti; M. Fabbi; G. Ferraioli; P. Prati; C. Filice; D. Sassera; C. Dalla Valle; C. Bandi; N. Vicari; P. Marone (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Reproductive development, GnRHa-induced spawning and egg quality of wild meagre (Argyrosomus regius) acclimatised to captivity - Neil Duncan; Alicia Estévez; Javier Porta; Ignacio Carazo; Fernando Norambuena; Cristobal Aguilera; Ignaci Gairin; Francesco Bucci; Roser Valles; Constantinos C. Mylonas (Fish Physiology and Biochemistry, 2012)

Numerical Study of the Neutral Atmospheric Boundary Layer Over Complex Terrain - Gilberto A. A. Moreira; André A. C. dos Santos; Carlos A. M. do Nascimento; Ramon M. Valle (Boundary-Layer Meteorology, 2012)

Somatic embryogenesis and organogenesis in apomictic and sexual Brachiaria brizantha - G. B. Cabral; V. T. C. Carneiro; A. L. Lacerda; C. B. do Valle; A. P. Martinelli; D. M. A. Dusi (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

500-year temperature reconstruction in the Mediterranean Basin by means of documentary data and instrumental observations - Dario Camuffo; C. Bertolin; M. Barriendos; F. Dominguez-Castro; C. Cocheo; S. Enzi; M. Sghedoni; A. della Valle; E. Garnier; M.-J. Alcoforado; E. Xoplaki; J. Luterbacher; et al. (Climatic Change, 2010)

The western Mediterranean climate: how will it respond to global warming? - Dario Camuffo; C. Bertolin; N. Diodato; M. Barriendos; F. Dominguez-Castro; C. Cocheo; A. della Valle; E. Garnier; M. -J. Alcoforado (Climatic Change, 2010)

Evidence of natural hybridization in Brachiaria humidicola (Rendle) Schweick. (Poaceae: Panicoideae: Paniceae) - Kellen Regina Boldrini; M. S. Pagliarini; C. B. Valle (Journal of Genetics, 2010)

Boundary Lipids In The Nicotinic Acetylcholine Receptor Microenvironment - Francisco J. Barrantes; V. Bermudez; M. V. Borroni; S. S. Antollini; M. F. Pediconi; J. C. Baier; I. Bonini; C. Gallegos; A. M. Roccamo; A. S. Valles; V. Ayala; C. Kamerbeek (Journal of Molecular Neuroscience, 2010)

Identification and characterization of large-effect quantitative trait loci for grain yield under lowland drought stress in rice using bulk-segregant analysis - Ramaiah Venuprasad; C. O. Dalid; M. Del Valle; D. Zhao; M. Espiritu; M. T. Sta Cruz; M. Amante; A. Kumar; G. N. Atlin (Theoretical and Applied Genetics, 2009)

Leaf structure of species from three closely related genera from tribe Crotoneae Dumort. (Euphorbiaceae s.s., Malpighiales) - B. de Sá-Haiad; A. C. C. Serpa-Ribeiro; C. N. Barbosa; D. Pizzini; D. de O. Leal; L. de Senna-Valle; L. D. R. de Santiago-Fernandes (Plant Systematics and Evolution, 2009)

Isolation and characterization of microsatellite markers for Brachiaria brizantha (Hochst. ex A. Rich.) Stap - L. Jungmann; A. C. B. Sousa; J. Paiva; P. M. Francisco; B. B. Z. Vigna; C. B. do Valle; M. I. Zucchi; A. P. de Souza (Conservation Genetics, 2009)

Dynamic searching in the brain - Eduardo Mizraji; Andrés Pomi; Juan C. Valle-Lisboa (Cognitive Neurodynamics, 2009)

Development of microsatellite markers for Brachiaria humidicola (Rendle) Schweick - L. Jungmann; B. B. Z. Vigna; J. Paiva; A. C. B. Sousa; C. B. do Valle; P. R. Laborda; M. I. Zucchi; A. P. de Souza (Conservation Genetics Resources, 2009)

Abnormal meiosis in tetraploid genotypes ofBrachiaria brizantha (Poaceae) induced by colchicine: its implications for breeding - A. B. Mendes-Bonato; M. Ferrari Felismino; A. M. Souza Kaneshima; C. Pessim; V. Calisto; M. Suely Pagliarini; C. Borges do Valle (Journal of Applied Genetics, 2009)

Radiation-Guided Targeting of Combretastatin Encapsulated Immunoliposomes to Mammary Tumors - Christopher B. Pattillo; Berenice Venegas; Fred J. Donelson; Luis Del Valle; Linda C. Knight; Parkson L.-G. Chong; Mohammad F. Kiani (Pharmaceutical Research, 2009)

An Ecological Risk Assessment of the Exposure and Effects of 2,4-D Acid to Rainbow Trout (Onchorhyncus mykiss) - J. F. Fairchild; K. P. Feltz; A. L. Allert; L. C. Sappington; K. J. Nelson; J. A. Valle (Archives of Environmental Contamination and Toxicology, 2009)

An Ecological Risk Assessment of the Acute and Chronic Toxicity of the Herbicide Picloram to the Threatened Bull Trout (Salvelinus confluentus) and the Rainbow Trout (Onchorhyncus mykiss) - J. F. Fairchild; K. P. Feltz; L. C. Sappington; A. L. Allert; K. J. Nelson; J. Valle (Archives of Environmental Contamination and Toxicology, 2009)

Grape marc compost: microbial studies and suppression of soil-borne mycosis in vegetable seedlings - Mila Santos; Fernando Diánez; Manuel González del Valle; Julio C. Tello (World Journal of Microbiology and Biotechnology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Detecting conservation benefits in spatially protected fish populations with meta-analysis of long-term monitoring data - C. Ojeda-Martinez; J. T. Bayle-Sempere; P. Sánchez-Jerez; A. Forcada; C. Valle (Marine Biology, 2007)

Role of the cyclooxygenase pathway in the protection against postischemic stunning in conscious sheep - Elena C. Lascano; Héctor F. del Valle; Jorge A. Negroni (Molecular and Cellular Biochemistry, 2006)

The Mantos Blancos copper deposit: an upper Jurassic breccia-style hydrothermal system in the Coastal Range of Northern Chile - L. E. Ramírez; C. Palacios; B. Townley; M. A. Parada; A. N. Sial; J. L. Fernandez-Turiel; D. Gimeno; M. Garcia-Valles; B. Lehmann (Mineralium Deposita, 2006)

Genetic characterization of Paspalum notatum accessions by AFLP markers - F. Espinoza; L. D. Daurelio; S. C. Pessino; E. M. Valle; C. L. Quarin (Plant Systematics and Evolution, 2006)

Persistence of invertebrate iridescent virus 6 in tropical artificial aquatic environments - A. Hernández; C. F. Marina; J. Valle; T. Williams (Archives of Virology, 2005)

Mitochondrial polymorphisms and susceptibility to type 2 diabetes-related traits in Finns - Karen L. Mohlke; Anne U. Jackson; Laura J. Scott; Erin C. Peck; Yong D. Suh; Peter S. Chines; Richard M. Watanabe; Thomas A. Buchanan; Karen N. Conneely; Michael R. Erdos; Narisu Narisu; Sareena Enloe; et al. (Human Genetics, 2005)

Development of a citrus genome-wide EST collection and cDNA microarray as resources for genomic studies - J. Forment; J. Gadea; L. Huerta; L. Abizanda; J. Agusti; S. Alamar; E. Alos; F. Andres; R. Arribas; J. P. Beltran; A. Berbel; M. A. Blazquez; et al. (Plant Molecular Biology, 2005)

Asynchronous meiotic rhythm as the cause of selective chromosome elimination in an interspecific Brachiaria hybrid - C. Risso-Pascotto; M.S. Pagliarini; C. Borges do Valle; L. Jank (Plant Cell Reports, 2004)

Absence of ischemic preconditioning protection in diabetic sheep hearts: Role of sarcolemmal KATP channel dysfunction - Héctor F. del Valle; Elena C. Lascano; Jorge A. Negroni; Alberto J. Crottogini (Molecular and Cellular Biochemistry, 2003)

Candidemia in a Tertiary Care Hospital: Epidemiology and Factors Influencing Mortality - H. Alonso-Valle; O. Acha; J. D. García-Palomo; C. Fariñas-Álvarez; C. Fernández-Mazarrasa; M. C. Fariñas (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Ischemic shortening of action potential duration as a result of KATP channel opening attenuates myocardial stunning by reducing calcium influx - Elena C. Lascano; Jorge A. Negroni; Héctor F. del Valle (Molecular and Cellular Biochemistry, 2002)

Arbutus unedo L. communities in southern Iberian Peninsula mountains - J.A. Torres; F. Valle; C. Pinto; A. García-Fuentes; C. Salazar; E. Cano (Plant Ecology, 2002)

Sequence comparison and phylogenetic analysis of fish nodaviruses based on the coat protein gene - L. Dalla Valle; E. Negrisolo; P. Patarnello; L. Zanella; C. Maltese; G. Bovo; L. Colombo (Archives of Virology, 2001)

A Trichoderma harzianum chitinase destroys the cell wall of the phytopathogen Crinipellis perniciosa, the causal agent of witches' broom disease of cocoa - Janice Lisboa De Marco; Luzia Helena C. Lima; Marcelo Valle de Sousa; Carlos R. Felix (World Journal of Microbiology and Biotechnology, 2000)

Pharmacokinetics of a Hematoregulatory Peptide (SK&F 107647) in Healthy Male Volunteers and in Patients with Colorectal or Pancreatic Adenocarcinoma Not Amenable to Standard Therapy - Parnian Zia-Amirhosseini; Robert Z. Harris; Hugh C. Cowley; Juan W. Valle; David R. Citerone; Venkata K. Boppana; Howard Scarffe; Philip Watson; Charles B. Davis (Pharmaceutical Research, 2000)

Duplication of the chromosome number of diploid Brachiaria brizantha plants using colchicine - A. A. Pinheiro; M. T. Pozzobon; C.B. do Valle; M. I. O. Penteado; V. T. C. Carneiro (Plant Cell Reports, 2000)

Hypericum perforatum L. extract does not inhibit 5-HT transporter in rat brain cortex - M. Gobbi; F. Dalla Valle; C. Ciapparelli; L. Diomede; P. Morazzoni; L. Verotta; S. Caccia; L. Cervo; T. Mennini (Naunyn-Schmiedeberg's Archives of Pharmacology, 1999)

Identification of a maize linkage group related to apomixis in Brachiaria - S. C. Pessino; J. P. A. Ortiz; O. Leblanc; C. B. do Valle; C. Evans; M. D. Hayward (Theoretical and Applied Genetics, 1997)

The Use of Human Hepatocytes to Select Compounds Based on Their Expected Hepatic Extraction Ratios in Humans - Th. Lavé; S. Dupin; C. Schmitt; B. Valles; G. Ubeaud; R. C. Chou; D. Jaeck; Ph. Coassolo (Pharmaceutical Research, 1997)